Attenuation of hyperlipidemia- and diabetes-induced early-stage apoptosis and late-stage renal dysfunction via administration of fibroblast growth factor-21 is associated with suppression of renal inflammation. - Chi Zhang; Minglong Shao; Hong Yang; Liangmiao Chen; Lechu Yu; Weitao Cong; Haishan Tian; Fangfang Zhang; Peng Cheng; Litai Jin; Yi Tan; Xiaokun Li; et al. (PLoS ONE, 2013)
BACKGROUND: Lipotoxicity is a key feature of the pathogenesis of diabetic kidney disease, and is attributed to excessive lipid accumulation (hyperlipidemia). Increasing evidence suggests that fibroblast growth factor (FGF)21 has a crucial role in lipid metabolism under diabetic conditions. OBJECTIVE: The present study investigated whether FGF21 can prevent hyperlipidemia- or diabetes-induced renal damage, and if so, the possible mechanism. METHODS: Mice were injected with free fatty acids (FFAs, 10 mg/10 g body weight) or streptozotocin (150 mg/kg) to establish a lipotoxic model or type 1 diabetic model, respectively. Simultaneously the mice were treated with FGF21 (100 µg/kg) for 10 or 80 days. The kidney weight-to-tibia length ratio and renal function were assessed. Systematic and renal lipid levels were detected by ELISA and Oil Red O staining. Renal apoptosis was examined by TUNEL assay. Inflammation, oxidative stress, and fibrosis were assessed by Western blot. RESULTS: Acute FFA administration and chronic diabetes were associated with lower kidney-to-tibia length ratio, higher lipid levels, severe renal apoptosis and renal dysfunction. Obvious inflammation, oxidative stress and fibrosis also observed in the kidney of both mice models. Deletion of the fgf21 gene further enhanced the above pathological changes, which were significantly prevented by administration of exogenous FGF21. CONCLUSION: These results suggest that FFA administration and diabetes induced renal damage, which was further enhanced in FGF21 knock-out mice. Administration of FGF21 significantly prevented both FFA- and diabetes-induced renal damage partially by decreasing renal lipid accumulation and suppressing inflammation, oxidative stress, and fibrosis.